A novel algorithm for adaptive NLMS beamformer. (2016) - Mini, P.R.; Mridula, S.; Paul, Binu; Mohanan, P.
This paper proposes a novel algorithm based on Mapped Real Transform for improving the convergence rate and reducing the computational complexity of Normalised Least Mean Square beamformer. Simulation results using the proposed One Dimensional Reduced Mapped Real Transform algorithm project an improvement over the conventional Normalised Least Mean Square beamformer by exhibiting a reduction in computational complexity and computation time with the added advantage of faster convergence. The proposed One Dimensional Reduced Mapped Real Transform algorithm based Normalised Least Mean Square beamformer also exhibits an improved performance in terms of faster convergence and reduced scattering when used with Rayleigh and Rician channels.